1974
DOI: 10.1111/j.1939-0025.1974.tb01152.x
|View full text |Cite
|
Sign up to set email alerts
|

A working model for mental health program evaluation.

Abstract: This paper describes a conceptual model of human service program evaluation, and integrates three key components of the evaluation process: a) Levels of Evaluative Activity, b) Functional Roles of the Evaluator, and c) Program Information Capability. This model has been useful in assessing evaluation capability of mental health programs, and in suggesting itineraries for enhancing evaluation capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1977
1977
1995
1995

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…To examine the data in terms of the hypothesized hierarchical model, evaluation activities were grouped by conceptual categories (Attkisson et al, 1974). Category indices were then calculated by taking the mean of the item indices in each category.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the data in terms of the hypothesized hierarchical model, evaluation activities were grouped by conceptual categories (Attkisson et al, 1974). Category indices were then calculated by taking the mean of the item indices in each category.…”
Section: Resultsmentioning
confidence: 99%
“…The earliest research to propose a data-based model of mental health evaluation performance was that of Attkisson and colleagues (Attkisson et al, 1974). In 1972, they observed evaluation in some 70 mental health facilities and proposed a developmental model of internal evaluation along three dimensions: evaluation activity, information capability, and functional role of the evaluator.…”
Section: Historical Contextmentioning
confidence: 99%
“…The purpose of developing the Evaluation Performance Questionnaire (EPQ) and the Evaluation Utilization Questionnaire (EUQ) was to create comprehensive, behaviorally specific, and interrelated assessment tools grounded in a particular conceptual model of mental health evaluation (Attkisson et al 1974;Attkisson and Hargreaves 1979) and specific to a type of agency setting (CMHCs).…”
Section: Instrument Developmentmentioning
confidence: 99%
“…Recently a program evaluation project (Attkisson, McIntyre, Hargreaves, Harris, & Ochberg, 1974) reported that their field survey of 80 managers, academicians, and clinicians revealed five major factors impeding the implementation of evaluations.This paper offers workable solutions to the five problems identified by Attkisson and his co-workers (1974). It has been our experience that these solutions do work and we feel they will prove workable in the majority of centers across the country.…”
mentioning
confidence: 99%